Pembuatan Pilar Support Mesin 3D Concrete Printing menggunakan Konstruksi Cremona dengan Material Besi Profil Siku - Nopriyanti, Rani; Fauzi, Muhammad; Setiawan, Heri; Kurniaji, Anhar (JTRM (Jurnal Teknologi dan Rekayasa Manufaktur), 2024)
The main constraint in porang processing are porang chips thickness uniformity and high calcium oxalate content. There are three stages of porang processing are washing, slicing, and boiling. The machine designed in this research combining the function of three machines : washing machine, slicer, and boiler. First, porang roots is placed into the hopper, then porang is cleaned using rotating washing brush with the translational movement of the screw conveyor. After that, porang is sliced and boiled in NaCl solution to reduce its calcium oxalate content. This research uses VDI 2222 design methodology including planning, conceptualizing, designing, and finishing. The design and validation process of critical components is carried out using CAE (Computer Aided Engineering) software. After going through the design process, a machine design was produced with a production capacity of 500 kg/hour.